Digital reproduction of historical building ornamental components: From 3D scanning to 3D printing - Xu, J.; Ding, L.; Love, Peter (Elsevier BV, 2017)
© 2017 Elsevier B.V. A combination of the three-dimensional (3D) scanning and cement mortar-based 3D printing technology is used to develop a novel process for reproducing a historical building ornamental component, which is traditionally labor intensive and expensive to construct. A hierarchical algorithm for model slicing and a modified scan line algorithm for nozzle path are developed and presented. To demonstrate the feasibility of the proposed digital reproduction process, a damaged cup-shaped individual plinth from the campus at the Huazhong University of Science and Technology (HUST) in China, is 3D scanned, re-modelled, and re-constructed using specific 3D printing technology. An estimation is implemented to the façade of the printed plinth as well as the scanning accuracy. The compressive strength of the printed plinth is tested and calculated, which resulted in 19.8 Mpa and 15.6 Mpa for its vertical and lateral directions, respectively. The reproduction evaluation indicates that the developed process provides the foundation and impetus for future work in the area of the digital reproduction of historical building ornamental components using 3D scanning and cement mortar-based 3D printing.